2018
DOI: 10.1177/1477750918790019
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ ethical decision-making: Does being a patient themselves make a difference?

Abstract: There is very little literature on the actual decision-making frameworks used by general practitioners with respect to ethical issues and virtually none on the impact of personal experiences of illness on this. This study aimed to investigate what these frameworks might be and if and how they were altered by doctors' own illness experience. Twenty general practitioners were recruited, 10 having had a previous serious medical illness and 10 having no such history. They participated in a semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The patients who are most at risk for engaging in negative health behaviors also tend to be less educated and less wealthy, thus complicating their access to care and potentially increasing the negative biases that their providers may hold, restricting the care that their providers may assign to them. However, when health professionals are able to empathize with their patients, experience similar situations as patients themselves, or are asked to imagine how their decisions may affect those patients, they tend to provide better care [2224, 39]. Engaging in a creative narrative writing intervention such as one presented here may be a relatively quick, economically viable way to improve patient relations and care in these most vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients who are most at risk for engaging in negative health behaviors also tend to be less educated and less wealthy, thus complicating their access to care and potentially increasing the negative biases that their providers may hold, restricting the care that their providers may assign to them. However, when health professionals are able to empathize with their patients, experience similar situations as patients themselves, or are asked to imagine how their decisions may affect those patients, they tend to provide better care [2224, 39]. Engaging in a creative narrative writing intervention such as one presented here may be a relatively quick, economically viable way to improve patient relations and care in these most vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…One method of increasing empathy is to share in a common experience. Research has demonstrated that when physicians experience a serious illness and become patients themselves, they develop increased empathy, place a greater emphasis on the patient’s preferences, and demonstrate a willingness to work with the patient through the decision-making process [22, 23]. Further, reflective writing, which seeks to draw out personal experience with illness, has also been a useful method of inducing this type of empathic personal reflection [24].…”
Section: Introductionmentioning
confidence: 99%
“…4 From research with doctor participants, disclosing their own illnesses is thought to reassure patients, improve communication, ease stress, create empathy and increase patient satisfaction. [4][5][6][7][8] Usually disclosure happens with a specific purpose in mind. 4 Such disclosures, if concerning healthy behaviours, can help to motivate patients to adopt similar habits 9 and improve medication adherence.…”
Section: What Gap This Fillsmentioning
confidence: 99%
“…5 The Jungian 'wounded healer' notion suggests that self-illness disclosures should be beneficial to patients, particularly if that illness has been successfully resolved, 10 yet several studies show doctors are anxious about whether to disclose such information. [4][5][6]11,12 There are concerns that inappropriate disclosures cause inappropriate emotional gratification for the doctor, 13 reduce the focus on the patient, 6 increased the risk of sexual involvement with patients, 14 reduce the doctor's privacy, 15 cause medico-legal issues regarding competency, 16 and potentially stigmatise the doctor (particularly with respect to less socially acceptable illnesses such as HIV or mental health issues). 5 Although general practitioners (GPs) are generally happy to disclose less personal information such as hobbies or interests, only 25% would consider disclosing a physical illness and 12.5% a mental illness.…”
Section: What Gap This Fillsmentioning
confidence: 99%
“…Interestingly, our respondents’ perspectives parallel what other qualitative studies have revealed about physicians’ opinions of disclosing their illnesses to patients. The desire among patients to have their experience taken seriously by their physicians was an important subtheme that emerged from our study, and physicians who have been patients themselves recount how their illnesses increase their empathy for their patients and make them better at identifying and addressing their patients’ medical and emotional needs (2429). Our respondents reinforced the notion that physician self-illness can positively impact care and communication, as the second most common response was that physicians who had chronic pain could offer distinct insights into treatment and management and thus be better clinicians.…”
Section: Discussionmentioning
confidence: 98%